Pengaruh Kombinasi Pupuk NPK Phonska dan Pupuk Kandang terhadap Pertumbuhan dan Produksi Tanaman Tomat (Lycopersicum esculentum Mill.) - Nuraini Nuraini; Yosefina Mangera; Amelia L Limbongan (Musamus University, 2019)
This study aimed to determine the influence of the combination of NPK fertilizer Phonska and manure on growth and tomato production in the Screen House, Faculty of Agriculture, Musamus University, from January to April 2013, this study uses the design of complete random which consisted of 6 treatments, P0 ( control / without NPK Phonska Fertilizer and cow manure) P1 (100% NPK Phonska and 0% manure) P2 (75% NPK Phonska + 25% manure) P3 (50% NPK Phonska + 50% manure) P4 (25% NPK Phonska + 75% manure) P5 (0% NPK Phonska + 100% manure) with three replications. The data were analyzed by analysis of variance and if there is a real difference then proceed with the least significant difference test. The results showed that combination treatment gives a noticeable effect on the level of 95% of the plant's height age of 49 HST in treatment P3 (50% NPK Phonska + 50% manure) and the average amount of fruit harvested in treatment P1 (100% NPK Phonska and 0 % manure) P2 (75% NPK Phonska + 25% manure) and P3 (50% NPK Phonska + 50% manure) as well as providing a significant influence on the amount of leaf age 49 and 56 HST in treatment P2 (75% NPK Phonska + 25% manure). Best treatment combination contained in the P2 combination treatment (75% + 25% Phonska NPK manure) which generated a total weight of the fruit harvest / treatment that is 7,59 kg while the lowest was found in the control treatment (without Phonska NPK fertilizer and manure) is 2,54 kg.